Development and Validation of Two-Tier Multiple Choice to Identify Measure Students’ System Thinking Skills in Dynamic Electricity - Endang Susilawati; Ida Hamidah; Nuryani Rustaman; Winny Liliawati (Universitas Lambung Mangkurat, 2026)
Dynamic electricity is important due to its function as a thinking tool for further electronic circuit analysis. It is an abstract concept that must be understood by students as well as by physics teachers. A study about developing a set of two-tier multiple-choice questions was conducted to measure the system thinking skill of a number of student-teachers using Design Development Research (DDR). The instrument has been tested for its validity through expert judgment and field testing on a number of student teachers (n=62). After studying dynamic electricity learning material that had been prepared before. Based on the r table, which is 0.2108, it was obtained that out of 25 two-level tests, 23 were valid and can be used to measure students' and teachers' systems-thinking skills. In addition, the instrument showed high reliability, with a Cronbach’s alpha coefficient of 0.840.